A Literature Review: The Relationship between Decreased Hemoglobin Levels or Anemia and Acute Myocardial Infarction - Arkam, Jihan Raihanah; Wisudawan, Wisudawan; Rajab, Risna (Newinera Publisher, 2025)
Coronary heart disease (CHD) remains the leading cause of cardiovascular disease, with an estimated contribution to 36% of global mortality by 2020. Acute myocardial infarction (AMI) arises due to an imbalance between myocardial oxygen supply and demand. Anemia exacerbates myocardial ischemia by reducing blood oxygen levels and increasing myocardial oxygen consumption. This study aims to examine the relationship between decreased hemoglobin levels or anemia and AMI patients. This literature review employed a systematic search strategy using the keywords Relationship, Hemoglobin Levels, Anemia, and Acute Myocardial Infarction in both Indonesian and English. Searches were conducted across accredited electronic databases indexed in SINTA, such as Biomed Central, Garuda Portal, Google Scholar, Elsevier/Clinical Key, PubMed, and other relevant academic sources. Findings indicate that anemia influences the prognosis of AMI, although differing perspectives persist within the literature. Further research is required to comprehensively evaluate the impact of anemia on AMI patients and to determine the optimal management strategies for improving clinical outcomes.